Lumbar Spondylolisthesis and Core Stabilization Exercise for Pain Relief - ปาลี, พงศธร; กุลครอง, พัชริดา (Journal of Health Science of Thailand, 2021)
Lumbar spondylolisthesis is commonly found in low back pain disorder. The common manifestation is the slip of superior level of vertebral body in forward direction compared to inferior level of vertebral body, which causing the abnormality of joints, ligaments, muscles, tendons, and neuromuscular control resulting in decreased core stability. It leads to back pain and difficulty in performing activities in daily living. Core stabilization exercise can enhance the activation of core muscles promoting the stability of the spine. This effect will help patients with lumbar spondylolisthesis in decreasing pain and effectively facilitating the activities of daily living.